PENGARUH LAMA PENYIMPANAN SETELAH DIPERAH TERHADAP pH, BERAT JENIS DAN JUMLAH KOLONI BAKTERI SUSU KERBAU - Elly Roza; Salam Aritonang (Universitas Andalas, 2006)
The aim of the present research was to study the quality changes of buffalo’s milk stored in different time period after milking. About 10 liters of fresh buffalo milk which were obtained from Lembah Gumanti, Solok district were used in the experiment. The milk was divided and placed into four groups and stored in room temperature for 4 different time periods: 2, 4, 6 and 8 hours immediately after milking. Parameter measured included: pH, specific gravity and colony number of bacteria. Data was statistically analyzed by variance analysis in Block Randomized Design (RBD) with 4 treatments and 5 replicates. The results indicated that there was significant effect (P<0.01) among the treatment on the characteristic of buffalo milk. It showed that increasing of the storage time after milking have decreased pH and increased specific gravity and bacteria count.